2022
DOI: 10.24952/tazkir.v8i1.5809
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Activeness and Obedience in Carrying Out Worship Against Social Piety of Students at Rambah Hilir High School, Rokan Hulu Regency

Abstract: This research aimed at knowing the effect of organizational activity and obedience in performing worship to student social piety at State Senior High School 2 Rambah Hilir District, Rokan Hulu Regency. It was a field research with quantitative approach. The samples of this research were 172 students at State Senior High School 2 Rambah Hilir District, Rokan Hulu Regency. Questionnaire and documentation techniques were used for collecting the data. Linear and multiple regression techniques were used for analyzi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…It indicates that workplace spirituality is an essential predisposition for employee contextual performance. These findings support and confirm previous research indicating that workplace spirituality has a significant impact on performance (Nwanzu & Babalola, 2021;Jena, 2021;Ekowati, 2022) and negate Lubis's (2022) findings that work effectiveness actually influences workplace spirituality.…”
Section: Hypothesis Testingsupporting
confidence: 89%
See 1 more Smart Citation
“…It indicates that workplace spirituality is an essential predisposition for employee contextual performance. These findings support and confirm previous research indicating that workplace spirituality has a significant impact on performance (Nwanzu & Babalola, 2021;Jena, 2021;Ekowati, 2022) and negate Lubis's (2022) findings that work effectiveness actually influences workplace spirituality.…”
Section: Hypothesis Testingsupporting
confidence: 89%
“…Another study indicated that performance impacts effectiveness (Jiang & Liu, 2015). Additionally, Lubis (2022) revealed that obedience as an indicator of work effectiveness has an impact on social piety which includes a sense of community as a workplace spirituality's parameter. These inconsistency of research results triggers research gaps that require scientific clarification.…”
Section: Introductionmentioning
confidence: 99%